2017
DOI: 10.3390/nu9121358
|View full text |Cite
|
Sign up to set email alerts
|

Amount, Distribution, and Quality of Protein Intake Are Not Associated with Muscle Mass, Strength, and Power in Healthy Older Adults without Functional Limitations—An enable Study

Abstract: To maintain muscle mass in older age, several aspects regarding the amount and distribution of protein intake have been suggested. Our objective was to investigate single and combined associations of daily protein intake, evenness of protein distribution across the three main meals, number of meals providing ≥0.4 g protein/kg body weight (BW), and number of meals providing ≥2.5 g leucine, with muscle mass, strength, and power in successful agers. In this cross-sectional study in 97 healthy community-dwelling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 64 publications
8
54
1
Order By: Relevance
“…Furthermore, women with a low skeletal muscle index (SMI) were found to ingest lower amounts of animal protein at breakfast in comparison with those with a high SMI [32]. However, no significant associations among protein eating patterns, muscle mass, and physical function were determined in successful agers [58]. Only one study investigated whether frailty was associated with protein intake across meals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women with a low skeletal muscle index (SMI) were found to ingest lower amounts of animal protein at breakfast in comparison with those with a high SMI [32]. However, no significant associations among protein eating patterns, muscle mass, and physical function were determined in successful agers [58]. Only one study investigated whether frailty was associated with protein intake across meals.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were recruited from the community via social communication (flyers and meetings in community centers) in the Great Montreal area. To be included in this study, subjects had to meet the following criteria: (1) aged 60 years and over, (2) inactive for at least 6 months (< 2 h/week of structured exercise), (3) obese [fat mass (FM): men > 25%, women > 35%; [40]], (4) a stable weight (± 2 kg) over the past 6 months, (5) no orthopedic limitations, (6) no counter-indication to practice physical activity (Physical Activity Readiness Questionnaire), (7) absence of menstruation for the past 12 months for women, (8) no smoker and, (9) no excessive alcohol consumers (≥ 2 drinks/day). Subjects with diagnosed (untreated) neurological, cardiovascular, lung diseases or cognitive disorders were also excluded.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Among the many etiological factors, several aspects of protein intake are thought to contribute to the decline in muscle mass, strength and quality during aging: daily amount, distribution over the day, per-meal amount and protein quality [5][6][7]. Firstly, the protein quality affects muscle synthetic response [8].…”
Section: Introductionmentioning
confidence: 99%
“…Higher protein intake was associated with greater muscle mass and less decline in muscle mass in most observational studies [12][13][14][15][16] but not all. 17 In addition, evidence from randomized clinical trials showed either beneficial or no effect of protein supplementation on preserving muscle mass in older adults. [18][19][20][21] Animal and plant protein may have a different effect on muscle health.…”
mentioning
confidence: 99%